Labor, health, social work and the middle classes: Do Spanish youth have to jeopardize their health to find a job? - Antonio López-Peláez (Social Work & Society, 2016)
In the sphere of the European Union, especially in countries of southern Europe, the economic crisis and the redefining of welfare state benefits have led to a scenario in which many young people encounter major difficulties in attaining and/or maintaining a middle-class lifestyle. Their life trajectories may be affected not only by wage or job insecurity, but also by occupational hazards due to poor working conditions. In this paper, we examine the changes in occupational safety and health in Spain. The results shed light on the precarious working conditions of Spanish youth; a key factor in the failed career paths of young people. For this reason, one of the priorities of social work intervention programs should be the prevention of occupational hazards and workplace health promotion. -- El trabajo, la salud, el trabajo social y las clases medias: ¿Tiene que poner en peligro la juventud española su salud para encontrar un trabajo? En el ámbito de la Unión Europea, la crisis económica y la redefinición de las prestaciones del Estado del Bienestar generan un escenario en el que los jóvenes experimentan severas dificultades para alcanzar y/o mantener el estilo de vida de las clases medias. En proceso de precarización creciente del mercado de trabajo, los jóvenes se encuentran en una situación difícil, y sus trayectorias vitales se pueden ver afectadas por los riesgos laborales que les afectan. En esta ponencia, analizamos la evolución de las condiciones de seguridad y salud en el trabajo en el caso español. Los resultados nos permiten arrojar luz sobre la precarización de las condiciones de vida de los jóvenes españoles, y su difícil acceso a las clases medias.